Murâbahah Li Al-Âmir Bi Al-Syirâ’ in the Perspective of Scholars: An Analysis of Contemporary World Fatwa - Herman, Marlinda; Muliadi (UIN Sulthan Thaha Saifuddin Jambi, 2025)
In classical fiqh, murâbahah is a simple sale and purchase contract that requires the seller to tell the truth about the cost and profit. This concept was later transformed in Islamic banking into murâbahah li al-âmir bi al-syira’, which introduced a credit sales system as a form of financing. This study reveals some contemporary world fatwas regarding the murâbahah li al-âmir bi al-syirâ’ contract with a qualitative-descriptive approach through library research. The results of the study show that there is ikhtilaf among contemporary scholars regarding the permissibility of the practice of this contract, with some critics calling the dominance of Murâbahah in Islamic banking products a ‘deviation from Islamic principles’ and encouraging Islamic banking to switch to a financing model based on profit loss sharing. However, some scholars in Islamic countries have issued fatwas accepting this contract with some stipulations that should not be violated by Islamic banks, otherwise, the validity of this contract should be doubted.